1985
DOI: 10.1113/jphysiol.1985.sp015537
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory synaptic potentials resulting from alpha 2‐adrenoceptor activation in guinea‐pig submucous plexus neurones.

Abstract: SUMMARY1. Intracellular recordings were obtained from neurones of the guinea-pig submucous plexus. Inhibitory synaptic potentials (i.p.s.p.s) were compared with hyperpolarizations evoked by brief, local applications of noradrenaline and by superfusion with adrenoceptor agonists.2. Hyperpolarizing potentials elicited by brief applications of noradrenaline were similar to the i.p.s.p. in latency of onset, amplitude, time course, conductance increase, reversal potential and ionic dependence. Both responses were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(100 citation statements)
references
References 29 publications
7
92
1
Order By: Relevance
“…Previous studies have characterized the i.p.s.p. recorded in normal preparations as being due to the action of NA released from sympathetic nerves onto a2-adrenoceptors on the submucosal neurones (North & Surprenant, 1985), although a non-adrenergic i.p.s.p. has also been observed (Mihara et al, 1987;Bornstein et al, 1988).…”
Section: Contractility Studiesmentioning
confidence: 95%
“…Previous studies have characterized the i.p.s.p. recorded in normal preparations as being due to the action of NA released from sympathetic nerves onto a2-adrenoceptors on the submucosal neurones (North & Surprenant, 1985), although a non-adrenergic i.p.s.p. has also been observed (Mihara et al, 1987;Bornstein et al, 1988).…”
Section: Contractility Studiesmentioning
confidence: 95%
“…Methods of dissection, intracellular recording from submucosal neurones, stimulation of interganglionic nerve fibres and optical measurements of arteriolar diameter have been described in detail previously (Surprenant, 1984;Neild et al, 1990 Ltd, 1990 nist; previous studies have shown that cumulative and noncumulative applications of UK 14304 produce similar hyperpolarizations in submucosal neurones (North & Surprenant, 1985;Surprenant & North, 1988). Schild plots were obtained from data on individual neurones and the dissociation equilibrium constants (KDs) and slopes so obtained were then averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Previous determinations of KD values for idazoxan, yohimbine and phentolamine for the receptors involved in postsynaptic hyperpolarization indicated that a homogeneous population of o2-adrenoceptors was present on submucosal neurones (North & Surprenant, 1985;Surprenant & North, 1988). Slopes of Schild plots for idazoxan, yohimbine, WB 4101 and ARC-239 to antagonize the UK 14304 inhibition of the nicotinic e.p.s.p.…”
Section: Presynaptic and Postsynaptic A2-adrenoceptors On Cholinergicmentioning
confidence: 99%
See 2 more Smart Citations